1999
DOI: 10.1080/00016489950181855
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Criteria for Central versus Peripheral Positioning Nystagmus and Vertigo: a Review

Abstract: Head positioning can lead to pathological nystagmus and vertigo. In most instances the cause is a peripheral vestibular disorder, as in benign paroxysmal positioning vertigo (BPPV). Central lesions can lead to positional nystagmus (central PN) or to paroxysmal positioning nystagmus and vertigo (central PPV). Lesions in central PPV are often found dorsolateral to the fourth ventricle or in the dorsal vermis. This localization, together with other clinical features (associated cerebellar and oculomotor signs), g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(41 citation statements)
references
References 14 publications
1
33
1
1
Order By: Relevance
“…While it is proposed that a central origin has to be assumed for pure upbeat, downbeat, and torsional nystagmus (1), we found that in about a one-third of cases (29.9%), CPN was a mixture of horizontal, torsional, and vertical components in variable combinations depending on the positioning maneuver performed. Furthermore, the direction of CPN is not always “atypical” for the plane of the canal being stimulated, since downbeat nystagmus was the most prominent direction during SHH (in 77.3%) while pHN was most prominent upon supine head turning (in 80.5%).…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…While it is proposed that a central origin has to be assumed for pure upbeat, downbeat, and torsional nystagmus (1), we found that in about a one-third of cases (29.9%), CPN was a mixture of horizontal, torsional, and vertical components in variable combinations depending on the positioning maneuver performed. Furthermore, the direction of CPN is not always “atypical” for the plane of the canal being stimulated, since downbeat nystagmus was the most prominent direction during SHH (in 77.3%) while pHN was most prominent upon supine head turning (in 80.5%).…”
Section: Discussioncontrasting
confidence: 53%
“…Maire and Duvoisin (11) found that, in a sample of 43 patients with static PN, the predictive value of the ocular fixation test was 94% ( n  = 35) for peripheral lesions and a 100% ( n  = 8) for central disorders, with the latter being associated with reduced optic fixation index. Buttner et al (1, 6) reported poor vestibular ocular reflex (VOR) suppression (6), while Williams et al (25) reported normal VOR suppression (25). Furthermore, Barber (14) reported pDBN, which was indeed enhanced with fixation, and Cobb and Friedman (18) reported nystagmus, which disappeared when fixation was removed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maire and Duvoisin (11) found that, in a sample of 43 patients with static PN, the predictive value of the ocular fixation test was 94% (n = 35) for peripheral lesions and a 100% (n = 8) for central disorders, with the latter being associated with reduced optic fixation index. Buttner et al (1,6) reported poor vestibular ocular reflex (VOR) suppression (6), while Williams et al (25) reported normal VOR suppression (25). Furthermore, Barber (14) reported pDBN, which was indeed enhanced with fixation, and Cobb and Friedman (18) reported nystagmus, which disappeared when fixation was removed.…”
Section: Fixationmentioning
confidence: 95%
“…Dangerous causes include neurologic mimics known as ‘central paroxysmal, positional vertigo’ (CPPV) (e.g., posterior fossa mass lesions 34 ) and serious causes of orthostatic hypotension, 35 such as internal bleeding. All are associated with episodic positional symptoms, but can be readily distinguished from one another using targeted bedside history and exam.…”
Section: Four Vestibular Syndromesmentioning
confidence: 99%